2007
DOI: 10.2320/jinstmet.71.801
|View full text |Cite
|
Sign up to set email alerts
|

Substance Flow Analysis on Diffused Toxics Contained in End-of-Life Cellular Phone

Abstract: Various low toxicity substances are contained in the high functional electronic products in recent years. Although there is a little quantity of low toxicity substances in each electronic product, total amount of them has been increasing by the mass production of electronic products. This means they tends to diffuse into environment and it also results in the loss of valuable metals.In this work, a substance flow analysis (SFA) on low toxicity substances in used cellular phones as a typical example of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The results of KPI-1 are related to [27], where a mobile application was developed for plastic waste recycling in Indonesia. The results showed that the use of factors such as personal attitude, perceived behavioral control, and perceived moral obligation helped to efficiently increase the participation and use of the application, as well as to create greater awareness about the culture of plastic recycling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of KPI-1 are related to [27], where a mobile application was developed for plastic waste recycling in Indonesia. The results showed that the use of factors such as personal attitude, perceived behavioral control, and perceived moral obligation helped to efficiently increase the participation and use of the application, as well as to create greater awareness about the culture of plastic recycling.…”
Section: Discussionmentioning
confidence: 99%
“…They sought to demonstrate that applications according to these metrics preserve the environment and have better performance. In [27], we developed a mobile application for plastic waste recycling in Indonesia, to promote a recycling culture in the Indonesian population. The results showed a significant increase in citizen participation and increased awareness about the plastic recycling culture.…”
Section: Related Workmentioning
confidence: 99%